The Future of Gamma-Ray Experiments in the MeV-EeV Range - Allen, Alice; Aramaki, Tsuguo; Alves Batista, Rafael; Benoit, Mathieu; et al (My University, 2021)
Naturally occurring particle accelerators shine brightly throughout the universe, inviting us to discover fundamental laws and hone our theories if we look in their directions with the right detectors. Gamma-rays, the most energetic photons, carry information from the far reaches of extragalactic space with minimal interaction or loss of information. They bring messages about particle acceleration in environments so extreme they cannot be reproduced on earth for a closer look. Gamma-ray astrophysics is so complementary with collider work that particle physicists and astroparticle physicists are often one in the same. Gamma-ray instruments, especially the Fermi Gamma-ray Space Telescope, have been pivotal in major multi-messenger discoveries over the past decade. There is presently a great deal of interest and scientific expertise available to push forward new technologies, to plan and build space- and ground-based gamma-ray facilities, and to build multi-messenger networks with gamma rays at their core. It is therefore concerning that before the community comes together for planning exercises again, much of that infrastructure could be lost to a lack of long-term planning for support of gamma-ray astrophysics. Gamma-rays with energies from the MeV to the EeV band are therefore central to mul tiwavelength and multi-messenger studies to everything from astroparticle physics with compact objects, to dark matter studies with diffuse large scale structure. These science goals and the excitement of new discoveries have generated a wave of new gamma-ray facility proposals and programs. Since the legacy of existing facilities is well covered in many other places, this paper highlights new and proposed gamma-ray technologies and facilities that have each been designed to address specific needs in the measurement of extreme astrophysical sources that probe some of the most pressing questions in fundamental physics for the next decade. The proposed instrumentation would also address the priorities laid out in the recent Decadal Survey of Astronomy and Astro-physics (Astro2020), a complementary study by the astrophysics community that provides opportunities also relevant to Snowmass.
Authors:  Alice Allen, Tsuguo Aramaki, Rafael Alves Batista, Mathieu Benoit, Peter Bloser, Jennifer Bohon, Aleksey E. Bolotnikov, Isabella Brewer, Michael S. Briggs, Chad Brisbois, J. Michael Burgess, Eric Burns, Regina Caputo, Gabriella A. Carini, S. Bradley Cenko, Eric Charles, Stefano Ciprini, Valerio D'Elia, Tansu Daylan, James Distel, Axel Donath, Wade Duvall, Henrike Fleischhack, Corinne Fletcher, Wen Fe Fong, Dario Gasparrini, Marco Giardino, Adam Goldstein, Sean Griffin, J. Eric Grove, Rachel Hamburg, J. Patrick Harding, Jeremy Hare, Boyan Hristov, C. Michelle Hui, Tess Jaffe, Pete Jenke, Oleg Kargaltsev, Christopher M. Karwin, Matthew Kerr, Dongsung Kim, Daniel Kocevski, John Krizmanic, Ranjan Laha, Niccolo Di Lalla, Jason Legere, Cristina Leto, Richard Leys, Fabrizio Lucarelli, Israel Martinez-Castellanos, Alessandro Maselli, M. Nicola Mazziotta, Mark McConnell, Julie McEnery, Jessica Metcalfe, Manuel Meyer, Alexander A. Moiseev, Reshmi Mukherjee, Michela Negro, Keiichi Ogasawara, Nicola Omodei, Ivan Peric, Jeremy S. Perkins, Matteo Perri, Carlotta Pittori, Gianluca Polenta, Daniel Poulson, Robert Preece, Giacomo Principe, Judith L. Racusin, Oliver Roberts, Nicholas L. Rodd, Peter Shawhan, Thomas Shutt, Clio Sleator, Alan Smale, John Smedley, Jacob R. Smith, Jay Tasson, Peter Teuben, John Tomsick, Peter Veres, Francesco Verrecchia, Zorawar Wadiasingh, Colleen A. Wilson-Hodge, Joshua Wood, Richard S. Woolf, Hui Yang, Bing Zhang, Haocheng Zhang, Andreas Zoglauer
Snowmass 2021
Editors: K. Engel, J. Goodman , P. Huentemeyer , C. Kierans , T.R. Lewis,,‡ , M. Negro, M. Santander, and D.A. Williams Authors:  Alice Allen, Tsuguo Aramaki, Rafael Alves Batista, Mathieu Benoit, Peter Bloser, Jennifer Bohon, Aleksey E. Bolotnikov, Isabella Brewer, Michael S. Briggs, Chad Brisbois, J. Michael Burgess, Eric Burns, Regina Caputo, Gabriella A. Carini, S. Bradley Cenko, Eric Charles, Stefano Ciprini, Valerio D'Elia, Tansu Daylan, James Distel, Axel Donath, Wade Duvall, Henrike Fleischhack, Corinne Fletcher, Wen Fe Fong, Dario Gasparrini, Marco Giardino, Adam Goldstein, Sean Griffin, J. Eric Grove, Rachel Hamburg, J. Patrick Harding, Jeremy Hare, Boyan Hristov, C. Michelle Hui, Tess Jaffe, Pete Jenke, Oleg Kargaltsev, Christopher M. Karwin, Matthew Kerr, Dongsung Kim, Daniel Kocevski, John Krizmanic, Ranjan Laha, Niccolo Di Lalla, Jason Legere, Cristina Leto, Richard Leys, Fabrizio Lucarelli, Israel Martinez-Castellanos, Alessandro Maselli, M. Nicola Mazziotta, Mark McConnell, Julie McEnery, Jessica Metcalfe, Manuel Meyer, Alexander A. Moiseev, Reshmi Mukherjee, Michela Negro, Keiichi Ogasawara, Nicola Omodei, Ivan Peric, Jeremy S. Perkins, Matteo Perri, Carlotta Pittori, Gianluca Polenta, Daniel Poulson, Robert Preece, Giacomo Principe, Judith L. Racusin, Oliver Roberts, Nicholas L. Rodd, Peter Shawhan, Thomas Shutt, Clio Sleator, Alan Smale, John Smedley, Jacob R. Smith, Jay Tasson, Peter Teuben, John Tomsick, Peter Veres, Francesco Verrecchia, Zorawar Wadiasingh, Colleen A. Wilson-Hodge, Joshua Wood, Richard S. Woolf, Hui Yang, Bing Zhang, Haocheng Zhang, Andreas Zoglauer Conference: Submitted to the Proceedings of the US Community Study on the Future of Particle Physics (Snowmass 2021)